2022
DOI: 10.3390/medicina58050644
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Kidney of Diabetic Patients

Abstract: Given the current state of COVID-19, it is crucial to reveal its evolving relationship with and effect on different body organ systems and their diseases. The severity and outcome of COVID-19 have a very complex relationship, especially to the vital organs including the kidney, either in their state of health or disease. Additionally, it is well known that diabetes affects the kidney, leading to diabetic nephropathy. The kidney is also affected by different pathological and immunopathological reactions with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The results of the study indicated that patients with diabetes (9.8%) were more likely to require admission to the ICU than patients without diabetes. These findings suggest that diabetes and poor glycemic control are significant risk factors for severe COVID-19 illness and are correlated with worse outcomes 5 . Furthermore, microvascular complications in patients with diabetes are linked to a worse prognosis in COVID-19 6 .…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The results of the study indicated that patients with diabetes (9.8%) were more likely to require admission to the ICU than patients without diabetes. These findings suggest that diabetes and poor glycemic control are significant risk factors for severe COVID-19 illness and are correlated with worse outcomes 5 . Furthermore, microvascular complications in patients with diabetes are linked to a worse prognosis in COVID-19 6 .…”
Section: Resultsmentioning
confidence: 88%
“…SARS-CoV-19 causes multiple organ damage; however, the kidney is more susceptible to damage due to the expression of ACE2 receptors, which the virus uses to gain entry into the cells 5 . A study published on 18 July 2020, investigated the expression of ACE2 in 49 biopsies of patients with diabetic kidney disease and found that the expression of ACE messenger RNA was significantly increased by a factor of two when compared to healthy control subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations